German Russian Conference on Forest Genetics - Proceedings - Ahrensburg, 2017 November 21-23 - Bernd Degen; Konstantin V. Krutovsky; Mirko Liesebach (Johann Heinrich von Thünen-Institut, 2018)
The practical applications of forest genetics contribute substantially to sustainable forest management. Genetic data on optimally adapted and productive provenances as well as intensive tree breeding help to produce high quality forest reproductive material. Recent advances in tree genomics and DNA-sequencing techniques provide variable and more efficient tools for application in forestry, such as marker assisted tree breeding, screening for genes responsible for adaptive and economically important traits, and tree improvement. In the last two decades, the application of highly variable gene markers has produced a lot of very useful data on the genetic diversity and genetic differentiation of genetic resources of important forest tree species. The recent advances in the development of gene markers for variable diagnostic purposes enable to improve DNA-tests on wood and forest reproductive material including better control for timber origin, species protection and early detection of dangerous infections and diseases. The German-Russian MaRussiA project is a good example of the application of the above mentioned techniques. The Project is focused on aspen (Populus tremula): https://www.thuenen.de/en/fg/projects/current-projects/marussia-gene-marker-for-aspen-in-russia. Objectives: One of the main objectives of the joint German-Russian conference was to communicate the current results and experiences obtained in the MaRussiA project to a group of Russian and German experts in this field. We expected to get valuable feedbacks and recommendations for the remaining tasks within the project. Further, we wanted to get an overview on the state of the art of forest genetic research in both countries. Based on this overview and experiences of past and ongoing co-operation projects, we wanted to identify knowledge gaps and to stimulate the future scientific research and cooperation on these fields in Russia and Germany. Conference venue: The conference was planned and organised by the Thünen Institute of Forest Genetics (Dr. BERND DEGEN, Dr. GEORG VON WÜHLISCH, and Dr. MATTHIAS FLADUNG) together with the George August University of Göttingen (Prof. Dr. KONSTANTIN V. KRUTOVSKY). The conference was held with 25 participants at the 'Hotel am Schloss' in Ahrensburg, Germany from 21th to 23th of November, 2017. Conference structure: General scope sessions: - Tree Breeding and Provenance Research - Genome Research - Population Genetics - DNAidentification methods for wood and forest tree material (for timber tracking, control of forest reproductive material, etc.) - Discussion on future collaborative projects. – – Die praktischen Anwendungen der Forstgenetik tragen wesentlich zur nachhaltigen Waldbewirtschaftung bei. Genetische Informationen zu optimal angepassten und produktiven Herkünften sowie intensive Forstpflanzenzüchtung helfen, qualitativ hochwertiges forstliches Vermehrungsgut zu produzieren. Jüngste Fortschritte in der Genomik von Bäumen und bei den DNA-Sequenzierungstechniken liefern variable und effizientere Werkzeuge für die Anwendung in der Forstwirtschaft, wie z. B. markerunterstützte Züchtung, Screening nach Genen, die für adaptive und ökonomisch wichtige Merkmale verantwortlich sind, und zur Verbesserung von Eigenschaften. In den vergangenen zwei Jahrzehnten hat die Anwendung hochvariabler Genmarker eine Menge sehr nützlicher Daten zur genetischen Vielfalt und genetischen Differenzierung genetischer Ressourcen wichtiger Waldbaumarten hervorgebracht. Die jüngsten Fortschritte in der Markerentwicklung für variable diagnostische Zwecke ermöglichen es, DNA-Tests an Holz und forstlichem Vermehrungsgut zu verbessern, einschließlich einer besseren Kontrolle des Holzursprungs, des Artenschutzes und der Früherkennung von gefährlichen Infektionen und Krankheiten. Das deutsch-russische MaRussiA-Projekt ist ein gutes Beispiel für die Anwendung der oben genannten Methoden. Das Projekt ist vorrangig auf die Zitter-Pappel (Populus tremula) ausgerichtet: https://www.thuenen.de/en/fg/projects/current-projects/marussia-gene-marker-for-aspen-in-russia. Ziele: Eines der Ziele der deutsch-russischen Konferenz bestand darin, die bisher beobachteten Ergebnisse und Erfahrungen des MaRussiA-Projekts einer größeren Gruppe von russischen und deutschen Experten auf diesem Gebiet der Forstgenetik und -pflanzenzüchtung zu vermitteln. Wir erwarteten wertvolle Rückmeldungen und Empfehlungen für die verbleibenden Aufgaben innerhalb des Projekts. Darüber hinaus wollten wir einen Überblick über den Stand der forstgenetischen Forschung in beiden Ländern erhalten. Auf diesem Überblick und den Erfahrungen aus vergangenen und laufenden Kooperationsprojekten beabsichtigten wir, Wissenslücken zu identifizieren und die zukünftige wissenschaftliche Forschung und Kooperation in diesen Bereichen in Russland und Deutschland anzuregen. Tagungsort: Die Tagung wurde geplant und vom Thünen-Institut für Forstgenetik (Dr. BERND DEGEN, Dr. GEORG VON WÜHLISCH, Dr. MATTHIAS FLADUNG) zusammen mit der George August Universität Göttingen (Prof. Dr. KONSTANTIN V. KRUTOVSKY) ausgerichtet. Die Tagung fand mit 25 Teilnehmern vom 21. bis 23. November 2017 im 'Hotel am Schloss' in Ahrensburg, Deutschland statt. Tagungsgliederung: Allgemeine Themen der Sessions: - Forstpflanzenzüchtung und Herkunftsforschung - Genomforschung - Populationsgenetik - DNA identification methods for Holz und Pflanzenmaterial (zum Holzherkunftsnachweis, Kontrollen von forstlichem Vermerhungsgut usw.) - Diskussion über eine Zusammenarbeit in künftigen Projekten.
urn:nbn:de:gbv:253-201810-dn060232-8
Keywords: 630; Forest genetics; forest tree breeding; Populus tremula; DNA; molecular marker; Forstgenetik; Forstpflanzenzüchtung; molekulare Marker